Influence of Herbicides on Phytotoxicity and Soil Dehydrogenase Enzyme Activity in Chickpea (Cicer arietinum L.) - Dewangan, Mamta; Diproshan; Singh, A. P.; Chowdhury, Tapas (International Journal of Bio-resource and Stress Management, 2016)
A field experiment was conducted at Indira Gandhi Krishi Vishwavidyalaya, Raipur, Chhattisgarh (C.G.), India, during rabi season of 2013-14 to find out effective herbicide in chickpea. Results revealed that among the herbicidal treatments, post-emergence application of metribuzin @ 250 g a.i. ha-1 and early post-emergence application of oxyfluorfen @ 125 g a.i. ha-1 has recorded phytotoxicity on chickpea plants at 3, 7 and 10 days after spraying of herbicides and resulted in 62.26 and 53.19% reduction in yield, respectively, over hand weeding twice. The significantly minimum dehydrogenase activity was also observed under post-emergence application of metribuzin @ 250 g a.i. ha-1 and early post-emergence application of oxyfluorfen @ 125 g a.i. ha-1. Whereas, among the herbicides, pre-emergence application of pendimethalin @ 1000 g a.i. ha-1 resulted in significantly higher dehydrogenase activity of experimental field. Hand weeding twice at 25 and 45 DAS and pre-emergence tank mix application of oxyfluorfen+metribuzin @ 125+350 g a.i. ha-1 were most appropriate in reducing the density and dry weight of weeds with the weed control efficiency of 90.43 and 74.31%, respectively. Further, the significantly higher yield attributes, seed yield, stover yield and harvest index registered under hand weeding twice at 25 and 45 DAS, followed by the treatment of oxyfluorfen+metribuzin @ 125+350 g a.i. ha-1 as pre-emergence. Net return and B:C ratio was also recorded maximum under pre-emergence tank mix application of oxyfluorfen+metribuzin @ 125+350 g a.i. ha-1.